Os (des)caminhos da reforma psiquiátrica: análise da Política Nacional de Saúde Mental Brasileira de 2016 a 2022 - Oliveira, Alda Venusia Alves de (2022)
This Dissertation, entitled “THE (DES)PATHS OF PSYCHIATRIC REFORM: analysis of the Brazilian National Mental Health Policy from 2016 to 2022”, has as its main motivation, to investigate the consequences of the “new” normative guidelines established by the federal government, in the particularity of 2016 to 2022, nationwide. This object of study first went through a digression on madness in different times and situations, as well as on the way of caring over time and up to the present, in the Brazilian scenario. Likewise, the objective is to contribute with an attentive and critical reading of the fabric of its social expressions in the social context, based on the effervescence of the Psychiatric Reform established in Brazil. The importance of this research is also revealed in the imperative to collaborate with the debate on the National Mental Health Policy in Brazil, in the current scenario and its repercussions for the general population. This discussion within society becomes essential, since understanding the diversity of interests in the face of sociopolitical complexity also implies identifying the consequences that have been occurring within the class struggle. In this way, the Dissertation aims to lay bare the ideological game that brings the National Mental Health Policy closer to the conservative field in Brazil. In recent years, this policy has been guided against all the achievements that, for more than thirty years, were being conquered in Brazil through movements and social struggles for the area of mental health. Thus, we intend to observe these (mis)paths through the critical dialectic methodological procedure that makes it possible to investigate reality and its contradictions in depth. The approach will be qualitative, bearing in mind that the proposed problem will be elucidated through a bibliographical and documentary review. Thus, the current methodology for the elaboration of the Dissertation on screen, proposes to analyze established laws and norms, in addition to relevant theoretical references for the production of the present work. The investigated documents and texts were located, mainly, through the world wide web, based on the work repositories of CAPES, Digital Bank of Theses and Dissertations; articles; specialized magazines; Federal Government websites and links; documentaries; mental health conferences; data from the Ministry of Health (MS), as well as classic and secondary bibliographical references on the subject. As for the research results, the current legislation is presented in an abusive and contradictory way, in the sense that there is an attempt to reimplement the hospital policy at the core of the Psychosocial Care Network. The so-called “industry of madness” returns to the Brazilian scene and brings with it all the ills of a time when the importance of caring is given to profit. Nowadays, this vision returns with more vehemence and is linked to the time when social rights lose the perspective of social insertion. The federal government's “new” proposal to persist with the old hospital-centric policy has become retrograde. Thus, it is not possible to watch impassively the construction of an authoritarian State that, while representing private interests, in favor of a type of market, also restricts the freedom of patients, based on a hygienist culture of the 19th century, and directs the empowerment of a medical class that reinforces support around hospitalization in psychiatric hospitals and their inhumane practices, such as electroconvulsive therapy.